Chemical analysis of a lunar meteorite by laser ablation mass spectrometry. (March 2020) - Frey, Samira; Wiesendanger, Reto; Tulej, Marek; Neuland, Maike; Riedo, Andreas; Grimaudo, Valentine; Moreno-García, Pavel; López, Alena Cedeño; Mohos, Miklós; Hofmann, Beda; Mezger, Klaus; Broekmann, Peter; et al.
Highlights: Demonstration of in situ composition measurements of rocks on planetary surfaces. Measurement of chemical maps of rocks from major to trace elements. Derived the mineralogical composition for individual grains of the rock. Measured the crystallization temperature and Pb/U age of zircon.